The Concept of Religious Moderation in the Qur'an (Maintaining the Unity of NKRI by Understanding the Value of the Qur'an) - La Ode Muh. Nanang Pribadi Rere (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Indonesia is a country with diverse ethnicities, traditions, and beliefs. History records that the founders of Indonesia came from different ethnicities, religions, traditions, languages, skin colors, and hair types. These differences did not diminish their spirit of unity in establishing an independent and sovereign Indonesia. Islam is a religion that pays great attention to social aspects. As the holy book, the Qur'an contains teachings that encourage good and proper social interactions (mu’amalat) with others without discrimination and emphasize moderation (tawasut), avoiding extreme inclinations to the right or left. Therefore, maintaining Indonesia’s unity requires a strong spirit and a proper understanding of Islam. This article examines the concept of religious moderation in the Qur'an. To construct and support the author's arguments, various opinions from different sources are cited. The findings documented in this article indicate that the Qur'an, as the holy book of Muslims, encourages good social interactions (mu’amalat) and promotes moderation (tawasut), avoiding extreme tendencies in any direction.